Impact analysis of the government policies on the production of cotton, sorghum and groundnut in New Halfa Agricultural Production Corporation, Kasala State, Sudan (2006-2010) - Alnagarabi1, Elsayed E.M; Babiker, Neimat O.I; . Mahguob, Imad A (Gezira Journal of Agricultural Science; Vol 12 No 1 (2014), 2014)
The main objective of this paper was to analyze the impact of government policies on production of cotton, sorghum and groundnut in New Halfa Agricultural Production Corporation during the period from 2006 to 2010 in terms of efficiency, competitiveness and comparative advantages. The study depended on secondary data and information collected from relevant sources and references. The policy analysis matrix (PAM) was adopted as an analytical model to achieve the study objective. Nominal protection coefficient of inputs, nominal protection coefficient of outputs, effective protection coefficient, profitability coefficient, domestic resources coefficient and international value added were calculated for the seasons under consideration. The study results indicated that cotton, sorghum and groundnut inputs were subjected to taxes, where on the other hand, the government policies provided incentives and favored the production of cotton, sorghum and groundnut in New Halfa Agricultural Production Corporation. Consequently, it could be concluded that, although the overall impact was negative, but the study results indicated that there were still comparative advantages of these crops in New Halfa Agricultural Production Corporation. The study recommended that the cultivated areas of cotton, sorghum and groundnut should be expanded in New Halfa Agricultural Production Corporation and input taxes should be reduced.